2012
DOI: 10.23939/chcht06.03.285
|View full text |Cite
|
Sign up to set email alerts
|

Gradiently Anisotropic Conducting and Magnetic Polymer Composites

Abstract: The character of the local electric resistance variations of film polymer composites on the basis of polyvinyl alcohol with graphite powder on the one hand and the magnetic susceptibility of the same polymer with nickel nano-particles on the other hand has been studied. It has been established that the changes of these parameters essentially depends on both initial shape of the films and on the direction of their orientation. It is concluded that the films of gradiently anisotropic polymer composites may be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As it was shown above in polymer composites containing conductive particles, an increase in the drawing degree leads to a gradual increase in the electrical resistance of composite, which is caused by a gradual reduction of volume concentration of conductive particles in the drawing direction. A similar reasoning is also valid for composites containing a magnetic filler [37][38][39][40].…”
Section: Zonal Graded Stretching Methods and Functionally Graded Matermentioning
confidence: 71%
See 2 more Smart Citations
“…As it was shown above in polymer composites containing conductive particles, an increase in the drawing degree leads to a gradual increase in the electrical resistance of composite, which is caused by a gradual reduction of volume concentration of conductive particles in the drawing direction. A similar reasoning is also valid for composites containing a magnetic filler [37][38][39][40].…”
Section: Zonal Graded Stretching Methods and Functionally Graded Matermentioning
confidence: 71%
“…The intensity of redistribution of concentration is proportional to the value of relative elongation in a given region of the sample. The features of distribution of concentration of functional filler in local areas directly affect the properties of these areas [37][38][39][40].…”
Section: Zonal Graded Stretching Methods and Functionally Graded Matermentioning
confidence: 99%
See 1 more Smart Citation
“…Resulting self-assembly of C/Co nanopowders caused changes in their concentration and modulation of local resistance along the radius of the sample, which was measured by a two-contact method as in our previous work [6] (Figs. 2-7).…”
Section: Resultsmentioning
confidence: 99%
“…The value of coercivity of pure NiNPs increased from 154.13 to 185.5 G, measured in the Ni-PS composite films, while the value of room temperature exchange bias (H EB ) decreases with increasing Ni content from 56.5 to 21.1 G. These results suggested strong coupling between the ferromagnetic phase and the disordered surface spins in the PS matrix. Magnetic susceptibility of thin films made of NiNPs with polyvinyl alcohol and graphite was experimentally studied by Aneli et al 51 Gradient distribution of NiNPs in the stretched direction resulted in equivalent change of magnetic properties. It was concluded that structural anisotropy was the main reason of anisotropy in magnetic properties of the composites.…”
Section: Magnetic Properties Of Ni Nanoparticlesmentioning
confidence: 99%